Knowledge Management and Talent Management as Drivers of Employee Performance: The Mediating Role of Job Satisfaction - Dyah Yuni Wulandari; Joko Suyono; Eman Setiawan (International Journal of Business, Economics & Financial Studies, 2025)
Employee performance is a critical factor influencing organizational competitiveness, particularly in manufacturing industries that require efficient knowledge utilization and skilled human resources. However, many organizations still face challenges in effectively managing organizational knowledge and employee talent, which may affect employee satisfaction and performance outcomes. This study aims to examine the influence of knowledge management and talent management on employee performance, with job satisfaction acting as a mediating variable. A quantitative explanatory research design was applied using a cross-sectional approach. The study was conducted in a plastic pallet manufacturing company in Sidoarjo, Indonesia, involving all 36 employees in the production department as respondents through a saturated sampling technique. Data were collected using structured questionnaires measured on a five-point Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that knowledge management and talent management both have positive and significant effects on employee performance. Additionally, knowledge management and talent management significantly influence job satisfaction, while job satisfaction itself positively affects employee performance. The mediation analysis further reveals that job satisfaction partially mediates the relationship between knowledge management and employee performance as well as between talent management and employee performance. These findings highlight the importance of integrating knowledge management and talent management practices with initiatives that enhance employee satisfaction in order to improve employee performance. The study contributes to the human resource management literature by providing empirical evidence from the manufacturing sector and offers practical implications for organizations seeking to strengthen employee performance through effective knowledge and talent management strategies.